“Bumil Temker” Ibu Hamil Tempel Stiker P4k - Raudhatul Hasanah; Putri Yuliantie; Sariyati Sariyati; Ika Friscila (FKIP, Universitas Palangka Raya, 2024)
The coverage rate of repeat visits for pregnant women's examinations (K4) is an indirect indicator of maternal mortality, but it can indicate the extent of access or reach to maternal health services and illustrate the opportunity to detect and treat high-risk pregnant women. Based on findings in the community, it was found that the implementation of the Childbirth Planning and Complication Prevention (P4K) Program with Stickers had not been achieved. Some pregnant women had not attached stickers and did not understand the importance of P4K stickers and the implementation of the P4K program. This Community Service Activity is in the form of a